Implementation of Maqashid Sharia Values in the Operational Practices of BMT Nusantara Sempu Branch Office: A Document Analysis and In-Depth Interview Study - Ahmad Harist Fauzi (Citakonsultindo, 2026)
This study aims to analyze the implementation of Maqashid Sharia values in the operational practices of BMT Nusantara Sempu Branch Office. A qualitative case study approach was employed, with data collected through in-depth interviews with BMT management personnel, including the Branch Manager, Account Officer Savings and Financing (AOSP), and Account Officer Financing (AOAP). Additional data were obtained through participant observation of daily operational activities and analysis of internal and external institutional documents. Data were analyzed through data reduction, data display, and conclusion drawing, while source triangulation was applied to ensure data validity. The findings reveal that the implementation of Maqashid Sharia is reflected in five principal dimensions. First, hifzh al-din (protection of religion) is demonstrated through compliance with Sharia principles in all products and contracts, adherence to DSN-MUI fatwas, and the integration of religious values into risk management decisions. Second, hifzh al-nafs (protection of life) is implemented through financing feasibility assessments, a persuasive and family-oriented collection system, and restructuring schemes for customers experiencing financial difficulties. Third, hifzh al-aql (protection of intellect) is realized through transparent contract information, Islamic financial literacy programs, and the prohibition of gharar, riba, and maysir. Fourth, hifzh al-nasl (protection of lineage) is reflected in productive financing, educational savings programs, and business development assistance. Fifth, hifzh al-mal (protection of wealth) is implemented through prudential financial management, transparent profit-sharing mechanisms, and the management of social funds. The study concludes that Maqashid Sharia has been integrated into BMT operations and serves as a practical foundation for Islamic microfinance governance at the local level.